2002
DOI: 10.1002/bip.10059.abs
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform‐Raman spectroscopic study of natural resins of archaeological interest

Abstract: Resins from several different genera are studied using Fourier transform (FT)-Raman spectroscopy. Tree resins can be broadly divided into those that contain diterpenoid components and those that contain triterpenoid components. The diterpenoid resins analyzed are from the genera Pinus, Cedrus, and Agathis (kauri resin) and the triterpenoid resins examined are samples from Pistacia, Boswellia (frankincense), and Commiphora (myrrh) genera. A protocol is developed to nondestructively distinguish diterpenoid and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…The spectra in Fig. 12 from the UC 70 shroud cover clearly show evidence of the presence of an organic component(s) in the bands around 3000 cm 1 and between 800 and 1600 cm 1 ; in the present case, it is suggested that these features are probably characteristic of a frankincense resin, 32,36 which was used in ancient funerary practices.…”
Section: Yellow Pigmentssupporting
confidence: 52%
“…The spectra in Fig. 12 from the UC 70 shroud cover clearly show evidence of the presence of an organic component(s) in the bands around 3000 cm 1 and between 800 and 1600 cm 1 ; in the present case, it is suggested that these features are probably characteristic of a frankincense resin, 32,36 which was used in ancient funerary practices.…”
Section: Yellow Pigmentssupporting
confidence: 52%
“…These Raman signals can also be assigned to monosubstituted benzene ring breathing ( C C modes. 3,35 With respect to the diterpenes, there is another intense peak located at ca 1601 cm 1 that is absent from the spectrum of cephalotaxine (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…These may be attributed to aromatic stretching ( C C conjugated with the carbonyl group (C O) and non-conjugated benzene stretching ( C C respectively. 3 With docetaxel, there is only the one medium shoulder at 1630 cm 1 . For baccatin, the strong ester peak exhibits a moderate shoulder feature at 1614 cm 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spectroscopic studies performed to date including Pyrolysis coupled to GC/MS (Py-GC/MS) [14][15][16][17][18], Fourier Transform Infrared (FTIR) Spectroscopy [19][20][21][22][23][24][25] and Raman Spectroscopy [26][27][28][29] among other techniques [30] have been focused on the identification of the Pinus resin by determining its characteristic footprints. Nevertheless, a spectroscopic study of the ageing process is expected to give very valuable additional information since, unlike GC/MS, it can detect macromolecules and it doesn't require any sample treatment such as dissolving or derivatization, to identify how molecular species are organized and which reactions or interactions exist among them.…”
Section: Introductionmentioning
confidence: 99%